The Role of Marketing Communication in Influencing the Decision to Buy Organic Crop Products in the Practical Garden of the Faculty of Agriculture, University of Nusa Nipa Indonesia - Elisabeth Yuvensia Paulina; Sarlina Noni (Peneliti.net, 2021)
As an agricultural country, the agricultural sector is the main sector in Indonesia. The agricultural sector is a strategic and potential sector in the development of the national economy. One of the priorities to achieve this goal is the development of organic crop commodities. Marketing communication can change the way consumers think and behave depending on the way the communication is conveyed by the marketing party. This study aims to determine how the role of marketing communication in influencing the decision to buy organic plant products in the garden of the Faculty of Agriculture. Sampling in this study was carried out by purposive sampling method with the sample in this study were 30 people as respondents. Testing this problem using quantitative descriptive analysis method with Rank Spearman data analysis. The results of this study indicate that in increasing competitiveness and consumer buying interest, of course, the role of marketing communication is quite influential in the decision to buy organic plant products.